2012
DOI: 10.1097/jsm.0b013e31823513e1
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetic Profile of Inhaled and Oral Salbutamol in Elite Athletes With Asthma and Nonasthmatic Subjects

Abstract: We found no significant difference in pharmacokinetic profile of inhaled and oral salbutamol between elite athletes with asthma and nonasthmatic subjects. Our results indicate that urine salbutamol concentrations should be corrected for urine specific gravity when evaluating doping cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 16 publications
2
43
3
Order By: Relevance
“…[12] Unlike Elers et al, [19] our previous work found this variability only modestly improved by correction for dilution. This was done to avoid any random error associated with measurement in urine as these are notoriously variable and correction for dilution remains problematic.…”
Section: Discussioncontrasting
confidence: 55%
“…[12] Unlike Elers et al, [19] our previous work found this variability only modestly improved by correction for dilution. This was done to avoid any random error associated with measurement in urine as these are notoriously variable and correction for dilution remains problematic.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, exercise‐induced sweat loss concentrates the urine, thus leading to a higher urine concentration of beta 2 ‐agonists . Adjustment of urine samples of beta 2 ‐agonists to a USG of 1.020 g/mL has been shown to be a way to correct for hydration status and to change the outcome from false negative to true positive doping test results and false positive to true negative . Sporer et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has attempted to examine the excretion of salbutamol administered by diferent routes including oral and inhaled [16,17] and across a range of acute doses from 200 μg and 800 μg [18] and repeated doses over several hours [19]. he current study is the irst to examine the urinary excretion of an acute, high dose in comparison with an intermediate dose following intermittent running in soccer players.…”
Section: Discussionmentioning
confidence: 99%